Clinical characteristics and economic burden of Alzheimer’s disease inpatients in Hubei Province, China: a retrospective analysis of hospitalization costs and length of stay - Chen, Siyi; Jia, Chenguang; Zhang, Liangzi; Shen, Yin; Zhou, Da; Li, Meng; Peng, Xinye; Liu, Wen (Frontiers in Public Health, 2025)
BackgroundThe rapid aging of the population in China has led to a significant increase in the incidence of Alzheimer’s disease (AD). This escalating trend has resulted in a substantial economic burden, posing a formidable challenge to society.MethodsThe study population comprised inpatients with AD in Hubei Province from January 2019 to December 2021. Comprehensive patient information was extracted from the provincial inpatient electronic system database. The data collected included age, gender, occupation, insurance type, method of hospital admission, diagnosis, length of stay (LOS), total medical expenses (TME), and discharge condition. Multiple linear regression analysis was employed to identify and analyze the factors influencing LOS and TME among AD patients.ResultsThe study encompassed a total of 22,301 AD patients. The mean age of the patients was 79.58 ± 10.12 years, with over 90% of the AD patients being 65 years or older. Male patients constituted 49.94% of the study population. The average LOS was determined to be 19.35 days. The mean TME per patient was calculated at US$2,593.38. A positive correlation was observed between medical expenses and patient age. Notably, the medical expenses for patients aged 85 years and above were 2.14 times higher than those for patients under 65 years. Of the total expenses, 57.04% were allocated to medication and service fees. Regarding comorbidities, infections, fractures, and cardiovascular diseases were identified as the top three cost drivers for AD inpatient hospitalization.ConclusionAge and insurance type were identified as key determinants of both LOS and TME. To address these issues, strategies should be implemented to expand medical insurance coverage and enhance daily care for AD patients. Furthermore, it is crucial to prioritize the prevention of infections, fractures, and cardiovascular diseases among AD patients. The implementation of comprehensive health policies focusing on drug pricing, diagnostic procedures, and service costs is essential to mitigate the economic burden associated with AD.